Physicochemical, Rheological, and Sensory Properties of Gluten-Free Cookie Produced by Flour of Chestnut, Date Seed, and Modified Starch - Mehrdad Mohammadi; Nasim Khorshidian; Mojtaba Yousefi; Amin Mousavi Khaneghah (Journal of Food Quality)
A gluten-free rice flour-based cookie was produced using different mixtures of chestnut flour (0, 30, 40, and 50%), date seed flour (0, 10, and 20%), and modified starch (0.3, 0.5, 0.6, and 0.9%). Physicochemical, rheological, and sensory properties of the prepared treatments were investigated. The results showed that moisture, specific volume, and dough viscosity were the lowest in control and the highest in treatment T1 containing 20% date seed flour, 30% chestnut flour, and 0.9% modified starch (P<0.05). The highest (22.15 N) and the lowest hardness (13.5 N) were obtained in the control and T1, respectively, both of which increased over the storage time (P<0.05). Regarding the texture characteristics of different dough treatments, the control illustrated the lowest adhesiveness and the highest hardness and chewiness. Sensory evaluation revealed that gluten-free treatments were acceptable from the consumers’ point of view. It was concluded that T1 as a gluten-free cookie had the highest quality.